2021
DOI: 10.1007/s40843-020-1667-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous-doped bimetallic sulfides embedded in heteroatom-doped carbon nanoarrays for flexible all-solid-state supercapacitors

Abstract: Flexible supercapacitors (SCs) have become a popular research topic due to their extra-long service life, foldability, and wearability. Nevertheless, their low energy density restricts their applications. Here, we synthesized phosphorus-doped bimetallic sulfides embedded in heteroatom-doped (N, S, and P) carbon shells (P-ZCS/HC) using a simple approach to create high-performance flexible electrodes. The three-dimensional architecture made by interlaced nanosheets was preserved, and raised nanoparticles appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…1c, the deconvoluted C 1s spectra confirm the presence of sp 2 C (284.4 eV), sp 3 C (285.1 eV), CvN/C-O (286.3 eV), and C-N/O-CvO (288.7 eV). 33 The N 1s spectra of NSC/CoS-2 and P-NSC/CoS-2 (Fig. 1d) can be fitted into four parts, which correspond to pyridinic N (398.4 eV), pyrrolic N (400.2 eV), graphitic N (400.9 eV), and oxidized N (402.5 eV).…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
“…1c, the deconvoluted C 1s spectra confirm the presence of sp 2 C (284.4 eV), sp 3 C (285.1 eV), CvN/C-O (286.3 eV), and C-N/O-CvO (288.7 eV). 33 The N 1s spectra of NSC/CoS-2 and P-NSC/CoS-2 (Fig. 1d) can be fitted into four parts, which correspond to pyridinic N (398.4 eV), pyrrolic N (400.2 eV), graphitic N (400.9 eV), and oxidized N (402.5 eV).…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
“…Due to the synergistic effect of N-doped C shells and P-doped metal sulfide, the resulting P-ZCS/HC possessed plentiful redox reaction sites, displays good conductivity and remarkable capacitance. [171] Making use of the solubility difference between the products, Yang et al demonstrated to selectively prepare cobalt sulfide quantum dots (Co 9 S 8 -QDs) in Zn-MOF derived NiCoZn-LDH nanaoarrays on carbon fiber (CF) for hybrid supercapacitor. [172] Figure 8a presents the synthesis strategy of the CF@NiCoZn-LDH/Co 9 S 8 -QD nanosheet array electrode and the possible mechanism of selective vulcanization.…”
Section: Metal Sulfide Nanoarraysmentioning
confidence: 99%
“…Due to the synergistic effect of N‐doped C shells and P‐doped metal sulfide, the resulting P‐ZCS/HC possessed plentiful redox reaction sites, displays good conductivity and remarkable capacitance. [ 171 ]…”
Section: Mof‐derived Nanoarraysmentioning
confidence: 99%
“…For the illustration, P-doped NiCo 2 S 4 was reported by phosphidation to reveal enhanced electrical conductivity and more diffusional channels due to the enlarged charge carriers and crystal defects, resulting in improved capacitive performance [206]. However, in most cases the fabrication process for both sulfidation/selenization and doping is timeconsuming and complicated as multi steps are involved during the synthesis process and may cause unwanted morphology and disordered interfaces or ruin the compound structure [18,206,207]. Therefore, a one-step synthesis process (i.e., phospho-sulfidation/phospho-selenization) could be an attractive strategy owing to lower cost, easier and less time-consuming procedures, and requisite for large-scale production than that of complicated multi-step fabrication processes [208,209].…”
Section: Heteroatom-doped Bmcsmentioning
confidence: 99%
“…Poor rate performance and low cycling stability owing to the slow reaction kinetics of larger ions (Na, K, and multi ions) in SIBs, PIBs, and multi-IBs are also limitations in their commercialization [10][11][12][13][14][15][16][17]. In the case of SCs, inferior energy density and low rate capability are critical issues [18][19][20]. The sluggish oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), bifunctional electrocatalysts with unsatisfactory activities for both ORR and OER, large overpotential, and insulating nature of discharge product in MABs are also very challenging.…”
Section: Introductionmentioning
confidence: 99%